(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about the influence of collaborative approach-based methods on pedagogical intentions in the training process of future teachers based on a collaborative approach. Changing the existing content and methods of training future teachers in a higher educational institution based on new requirements, as well as approaches aimed at developing the educational process of methods based on the collaborative approach of the teacher and the student, are discussed. The study also paid special attention to the types of lessons and highlighted their various situations. For a deeper understanding of the essence of pedagogical intentions, the methods used in the educational process are considered individually. Ask future teachers about the importance of taking into account students’ cognitive abilities and interests and forming skills based on educational principles when organizing the process of teaching subjects based on collaborative approach methods.